University students' perception of teacher academic integrity in a Nigerian university (2007)
The paper examined the meaning of academic integrity from various perspectives and listed the components of academic integrity as found in some literature, and also the factors militating against integrity. The researchers developed and validated a 28-item checklist of what students perceive to be characteristics of teachers academic integrity. A sample of one hundred students across various strata via: ( diploma,undergraduate and postgraduate) from three Faculties and the Institute of Education was used in the study. The main findings were: The students placed high premium on teacher academic integrity, were unwilling to be given assignments, and did not want feedback so that their weakness would be unrevealed. Among the recommendations made were: that an academic integrity programme be established and the machinery for its enforcement set up such that complainants would be protected.